Applicability of Selected 3D Printing Materials in Electrochemistry - Choińska, Marta; Hrdlička, Vojtěch; Dejmková, Hana; Fischer, Jan; Míka, Luděk; Vaněčková, Eva; Kolivoška, Viliam; Navrátil, Tomáš (Biosensors, 2022)
This manuscript investigates the chemical and structural stability of 3D printing materials (3DPMs) frequently used in electrochemistry. Four 3D printing materials were studied: Clear photopolymer, Elastic photopolymer, PET filament, and PLA filament. Their stability, solubility, structural changes, flexibility, hardness, and color changes were investigated after exposure to selected organic solvents and supporting electrolytes. Furthermore, the available potential windows and behavior of redox probes in selected supporting electrolytes were investigated before and after the exposure of the 3D-printed objects to the electrolytes at various working electrodes. Possible electrochemically active interferences with an origin from the 3DPMs were also monitored to provide a comprehensive outline for the use of 3DPMs in electrochemical platform manufacturing.
Keywords: Electrodes; 3D tisk; Electrochemistry; Printing, Three-Dimensional; elektrody; anodic stripping voltammetry; chemical stability; cyclic voltammetry; elektrochemie; electrochemistry; differential pulse voltammetry; mechanical stability; 3D printing materials